2010
DOI: 10.1038/nsmb.1758
|View full text |Cite
|
Sign up to set email alerts
|

Munc13 C2B domain is an activity-dependent Ca2+ regulator of synaptic exocytosis

Abstract: Munc13 is a multidomain protein of presynaptic active zones that mediates the priming and plasticity of synaptic vesicle exocytosis, but the mechanisms involved remain unclear. Here, we use biophysical, biochemical, and electrophysiological approaches to demonstrate that the central C2B-domain of Munc13 functions as a Ca2+-regulator of short-term synaptic plasticity. The crystal structure of the C2B-domain revealed an unusual Ca2+-binding site with an amphipathic α-helix. This configuration confers onto the C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
312
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(356 citation statements)
references
References 73 publications
18
312
2
2
Order By: Relevance
“…Given that the contributions of PLC-dependent and -independent mechanisms to superpriming are partially mutually occlusive, we propose that these two mechanisms converge on the same regulatory protein or process. Munc13s are the only priming proteins with regulatory domains that sense Ca 2+ and DAG (11,12,18,19). Therefore, our results indicate that the recovery of τ fast is controlled by the activity of Munc13s, and support the notion that molecular priming mechanisms (i.e., superpriming) are responsible for the recovery of τ fast .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Given that the contributions of PLC-dependent and -independent mechanisms to superpriming are partially mutually occlusive, we propose that these two mechanisms converge on the same regulatory protein or process. Munc13s are the only priming proteins with regulatory domains that sense Ca 2+ and DAG (11,12,18,19). Therefore, our results indicate that the recovery of τ fast is controlled by the activity of Munc13s, and support the notion that molecular priming mechanisms (i.e., superpriming) are responsible for the recovery of τ fast .…”
Section: Discussionsupporting
confidence: 81%
“…It was shown that recovery of the FRP after prolonged depolarization is slowed down in calyces of such mice, mimicking block of CDR. In contrast, a gain-of-function mutation of the C2B domain of ubMunc13-2 increases vesicular release probability (18). These reports imply that the interaction of DAG and Ca 2+ with the C1 and C2B domains of Munc13s may have preferential effects on superpriming, whereas the Munc13-CaM interaction is one of the prerequisites for CDR.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The involvement of calcium-sensitive isoforms suggests that PKC responds to Ca res to produce PTP, possibly by phosphorylating Munc18-1 to alter the effective pool size and the probability of release (Nili et al 2006;Toonen et al 2006;Toonen and Verhage 2007). Munc13, a calciumsensitive presynaptic protein that regulates the priming and probability of release of vesicles, has been shown to influence short-term synaptic plasticity during and following tetanic activation (Brose and Rosenmund 2002;Junge et al 2004;Beierlein et al 2007;Shin et al 2010). It is influenced by many of the pharmacological agents that regulate PKC, and has been proposed as an alternative to PKC as a mediator of PTP and augmentation.…”
Section: Short-term Presynaptic Plasticitymentioning
confidence: 99%
“…(B) Le domaine C2A de Syt1 et par extension d'autres domaines C2 sont des domaines de liaison au Ca 2+ ,à repliement autonome. Les données illustrent la régulationà haute affinité et la forte coopérativité de la liaison des phospholipides au domaine C2A de Syt1 recombinant et purifié (reproduit de Davetlov & Südhof, 1993 Corbalan-Garcia et Gomez-Fernandez, 2014 Shin et al, 2010). Les domaines C2 sont donc des modules protéiques versatiles qui sont le plus souvent des domaines de liaison aux phospholipides mais peuvent adopter de multiples autres fonctions.…”
Section: Le Déclenchement De La Fusion Par Le Ca 2+ : Les Synaptotagmunclassified